Meningkatkan Aktivitas dan Hasil Belajar PKn Dengan Model Pembelajaran Kooperatif Group Investigation (GI) pada Materi HAM di Kelas XI SMA Negeri 1 Muaro Jambi - Refdawati Refdawati (Jurnal Ilmiah Dikdaya, 2019)
This study aims to improve the students’ activities and learning outcomes of Civics (PKn) subject by using the Cooperative learning model Group Investigation (GI) type, therefore learning is not only focused on teacher-centered but more emphasis on student activity. The study was designed as a classroom action research; with the research subjects were XI grade students of SMA Negeri 1 Muaro Jambi academic year 2017/2018 with 30 total number of students. This research was carried out in 2 cycles. Each published cycle, namely: (1) Planning, (2) Action, (3) Observation, and (4) Reflection. Data was taken using written tests, assessment sheets consisting of teacher activity observation sheets, active student observation sheets, and evaluation results. The results of the study show that indicators of success can be achieved in cycle 2, both from observing the activities of teachers in lesson preparation, observing student activities in attending lessons, and evaluating student learning outcomes. Students give positive responses to learning that are proven by students’ happiness in the classroom and students’undertsanding toward the lesson. This can be seen on the improvement of learning outcomes and supporting groups that are getting better. The conclusion was that the GI type cooperative learning model could improve students’ learning activities and outcomes in class XI of SMA Negeri 1 Muaro Jambi. The students are more enthusiastic in learning Civic (PKn), and become more active students in learning. The atmosphere of the investigation class encourages students to discuss and deepen their way of thinking by finding various alternative thoughts. The application of the GI type cooperative learning model can improve learning outcomes in class. This can be seen from the results of evaluations that show an improvement on students’ learning outcomes from 42.85% or 12 people (in the first cycle) to 92.86% or 26 people (in the second cycle). For the next researchers, it is suggested that the GI type cooperative learning model can be applied in teaching and learning activities in other high schools, so students can achieve maximum learning outcomes. The supervision program, empowering the MGMP, writing scientific journals, conducting research, taking part in an internship program and collaborating with colleagues.